Comparison of porcine versus bovine pericardial bioprosthesis in the mitral position. Issue 8 (12th May 2021) - Tsubota, Hideki; Sakaguchi, Genichi; Arakaki, Ryoko; Marui, Akira
Abstract: Background: There are no reports of midterm outcomes after mitral valve replacement with a 25‐mm bioprosthesis in a large series of patients. This study aimed to examine perioperative and midterm outcomes of bioprosthetic valve choice, porcine or bovine pericardial, in the mitral position, focusing on 25‐mm valves. Methods: From 2007 to 2018, 467 patients received a mitral bioprosthesis, with or without concomitant procedures. Of these, 111 (23.8%) were porcine, and 356 (76.2%) were bovine pericardial, and 219 patients (46.9%) received a 25‐mm valve. A propensity‐matched cohort of 192 patients was used for outcome analyses. The influence of the valve type on midterm survival and incidence of cardiac death was assessed. Similarly, subanalysis stratified by valve size was conducted. Results: In matched patients, there were no differences in midterm survival and incidence of cardiac death between the two groups (log‐rank test; p  = .268 and p  = .097, respectively). There were no differences in midterm survival and incidence of cardiac death between the 25‐mm valve and larger valve (log‐rank test; p  = .563 and p  = .597, respectively). The Cox proportional‐hazards model revealed that the valve type and 25‐mm valve did not affect midterm survival ( p  = .487 and p  = .375, respectively) and incidence of cardiac death ( p  = .678 and p  = .562, respectively). Conclusions: The choice of a porcine or bovine pericardial bioprosthesis does not affect midterm survival and cardiac death. The 25‐mm valves, whether bovine or porcine, could be an appropriate alternative when the patient's body size is small.